(untitled) (Texas Journal of Medical Science, 2024)
in patients with reactive arthritis (ReA), cytokines produced by Th17 cells, one of them IL17, affect cell differentiation, recruitment, activation of immune cells, and release of antimicrobial peptides. Among the cytokines of the IL-17 family, it is IL-17A that is of decisive importance in the induction of pathological bone resorption through direct activation of osteoclast precursors during the formation of the articular syndrome The aim of our work was to study the distribution of allele and genotype frequencies of the polymorphic region G197A (rs2275913) of the IL-17A gene in patients with ReA. As a result of the study, there were no significant differences in the distribution of alleles of the G197A polymorphism of the IL-17A gene in patients with ReA and apparently healthy people. But when comparing genotypic variants, we revealed differences: healthy GG and mutant AA genotypes were more common in patients, while the heterozygous GA genotype was more common in healthy people